2021
DOI: 10.14569/ijacsa.2021.0120856
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Extraction and Data Visualization: A Proposed Framework for Secure Decision Making using Data Mining

Abstract: The decision-making process, promptly on time, is a crucial success factor in large organizations. Generally, the data warehouses of these organizations grow rapidly with the data generated from various business activities. This huge volume of data needs to be analyzed and decisions must be made quickly to meet the market challenges. Accurate knowledge extraction and its visualization from big data can guide decisionmakers to conduct key analysis and make correct predictions. This paper proposes a decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…On the other hand, another study found that presenting information in charts rather than tables improved physicians' ability to identify outliers [ 41 ]. Recent research showed that healthcare providers can more efficiently identify trends and make decisions when laboratory data are presented in graph form [ 42 ]. The advent of interactive data visualization has enabled improved data insight through visualizations and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study found that presenting information in charts rather than tables improved physicians' ability to identify outliers [ 41 ]. Recent research showed that healthcare providers can more efficiently identify trends and make decisions when laboratory data are presented in graph form [ 42 ]. The advent of interactive data visualization has enabled improved data insight through visualizations and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Careful analysis and application are crucial. The sheer volume of data can overwhelm educators if not effectively managed (Adjerid & Kelley, 2018;Alshareef et al, 2021;Baesens, 2012;boyd & Crawford, 2012;Chen & Zhang, 2014;Cheung & Jak, 2018;Daniel, 2014Daniel, , 2017Harlow & Oswald, 2016;Huang et al, 2019;Kalgotra & Sharda, 2021;Klašnja-Milićević et al, 2017;Lazer et al, 2014;Luan et al, 2020;Lutfi et al, 2023;Renz & Hilbig, 2020;Sivarajah et al, 2017;Tsai et al, 2020). So it left an unanswered question: how can BDA be utilised effectively without overwhelming educators, and how can the insights be applied to improve educational outcomes?…”
Section: Introductionmentioning
confidence: 99%